E-Learning of Static Fluids Utilising Problem-Based Learning via the Edukati Platform to Encourage Students' Critical Thinking Skills - Satrio, Wahyu; Sianturi, Tiara Febi Anggini; M. Rahmad (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
This study aims to develop e-learning media based on Problem Based Learning (PBL) with the help of the Edukati platform on static fluid material to train students' critical thinking skills. The problems in this study are the low empowerment of critical thinking skills in physics learning and the lack of learning media that support independent and contextual understanding of concepts. The research employed the Research and Development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Validation was conducted by four experts (media expert, subject matter expert, technical expert, and pedagogical expert), and practical testing involved teachers and students from MA Muhajirin Kampar. The e-learning platform is equipped with videos, e-modules, e-worksheets, interactive quizzes, discussion forums, and exams aligned with PBL syntax and critical thinking indicators. The validity results from media, content, technical, and pedagogical experts yielded an average validity score of 3.52, indicating that the developed e-learning platform is highly valid. The responses from teachers and students showed enthusiasm and comfort with the developed media, achieving an average practicality score of 3.62 (very practical) and 3.55 (very practical). Therefore, the PBL-based Fluid Statics e-learning is suitable for enhancing critical thinking skills among high school/MA students in grade XI.